The Implication of Vat Regulation to Tax Revenues: the Case of Small Retailer in Indonesia - Inasius, Fany (Bina Nusantara University, 2013)
According to the VAT Act the category of small enterpreneur is an entrepreneur who attempts the circulation does not exceed 600 million rupiah, while according to the Income Tax Act is a business entrepreneur who has the total of revenues no more than 4.8 billion rupiah. The small retaillers with sales revenue above 600 million and below 4.8 billion rupiah which Income Tax Act could use the special rate of 0.75% of the total revenues required to levy VAT at 10% of sale revenues or when under 1.8 billion rupiah Â the VAT rate is of 3-4%. The imposition of value added tax which unfairly results in the lower level of taxpayer compliance. This study focuses on the implications of VAT rates on the small retailler who has the circulation of business between 600 million to 4.8 billion rupiah to the amount of tax revenue. From the research conducted based on the comparatives research method, the descriptive analysis of documents and interviews produced that the reduction in the VAT rate impacts in increased state revenue.